Influence of biologicaly active plant of kind solanaceae in phytopathogenic fungi - I. K. Aibulatova; O. V. Iagodkina; S. V. Eremeeva; V. E. Аfanasev (Юг России: экология, развитие, 2015)
This work is important as the plant of kind Solanaceae have a number of factors phytoimmunity of complex biologically active substances. The influence on micromycetes biologically active substances of these plants is of interest, since the latter can serve as an alternative means of protecting plants from pathogens. Tasks thesis were to determine toxigenicity and phytotoxicity collection fungal strains, the allocation of biologically active substances from the nightshade and potato and study their effects on phytopathogenic micromycetes.